PP-TPE adhesive-free composite material, preparation method and application thereof
Patent Information
- Application Number
- CN202611182379.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-05
- Publication Date
- 2026-10-09
AI Technical Summary
上述产品的售后数据显示,该坐垫在湿热环境下使用6-12个月后,界面处出现白油富集现象,形成弱油层,逐步破坏界面结合,导致分层、脱粘
1.本申请采用反应性聚异丁烯增塑剂替代部分白油,该增塑剂主链为饱和聚异丁烯结构,与氢化苯乙烯-丁二烯-苯乙烯嵌段共聚物的橡胶相相容性良好,可插入橡胶相软段中起到增塑作用,维持坐垫表面柔软触感。同时,因其分子量低且与橡胶相容但非化学键合,在热循环中具有向界面迁移的热力学驱动力,迁移至界面后其侧链酸酐基团可与来自PP基体层的环氧基发生开环酯化反应,形成共价酯键。这样,原本破坏界面的白油迁移过程转变为建设界面的化学桥接过程,使坐垫在长期使用中实现界面的持续增强。
Smart Images

Figure CN122878709A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polymer technology, specifically relating to a PP-TPE adhesive-free composite material, its preparation method, and its application. Background Technology
[0002] PP-TPE composite material is a two-layer structure material with polypropylene (PP) as the rigid matrix and thermoplastic elastomer (TPE) as the flexible functional layer. It is widely used in cushion products such as furniture, car seats, and sports equipment. This material combines the high strength and heat resistance of polypropylene with the soft touch and bending resistance of thermoplastic elastomer. Through a one-piece molding process, it can produce seat cushions with dual hardness—soft on the surface and supportive in the core—meeting the needs of ergonomics and long-term seating comfort. In the automotive seating industry, one-piece molded seat cushions have become standard equipment in mid-to-high-end models. The surface TPE provides a soft touch and anti-slip properties, while the core PP provides structural support and dimensional stability. The overall weight is lighter than traditional foam seat cushions, and it is recyclable, aligning with the trends of lightweighting and environmental protection in the automotive industry.
[0003] In existing technologies, traditional seat cushions typically use separately injection-molded or molded PP frames and TPE padding, which are then bonded together using polyurethane adhesives or hot melt adhesives. This process suffers from high volatile organic compound (VOC) emissions from adhesives, poor environmental performance, cumbersome procedures, and high labor costs. Furthermore, the adhesive layer is prone to aging and embrittlement over long-term use, leading to interface cracking and delamination when the cushion is bent, affecting its lifespan and safety. The EU REACH regulation is increasingly stringent on the VOC content of automotive interior parts, making traditional adhesive processes insufficient to meet the environmental compliance requirements of exported vehicles.
[0004] To address the aforementioned issues, dual-injection molding technology has been introduced into the seat cushion manufacturing industry in recent years. This technology uses a dual-injection molding machine. First, TPE melt is injected into the mold to form a soft surface layer. Then, by switching between a mold turntable and a slider, PP melt is injected and melts with the TPE surface layer at the interface. After cooling and solidification, a glue-free composite seat cushion is obtained. A car seat supplier used this process to produce one-piece molded seat cushions, eliminating the adhesive process and improving production efficiency and environmental friendliness to some extent. However, in actual mass production, the supplier found that after 100,000 bending fatigue tests, the PP-TPE interfacial peel strength decreased by more than 50%. Cross-sectional analysis revealed that the TPE surface from the first injection formed a dense crystalline skin approximately 20-30 μm thick under mold cooling. This skin layer had extremely low molecular chain mobility, preventing the second injection of PP melt and compatibilizer from penetrating. The interface only formed a shallow physical contact, and the insufficient molecular chain entanglement density led to stress concentration and interfacial peeling during repeated bending.
[0005] Some products add white oil to the TPE functional layer to adjust hardness and softness. However, white oil is a small-molecule alkane, compatible with hydrogenated styrene-butadiene-styrene block copolymer rubber but not chemically bonded. Under the thermal cycling and stress of long-term use of the cushion, white oil has a thermodynamic tendency to migrate to the interface. After-sales data of the above-mentioned products show that after 6-12 months of use in a humid and hot environment, white oil enrichment appears at the interface, forming a weak oil layer, gradually destroying the interfacial bond, leading to delamination and debonding. Existing technologies usually delay migration by increasing the amount of compatibilizer or using high-viscosity white oil, but increasing the amount of compatibilizer will lead to increased TPE hardness and worsened feel, while high-viscosity white oil has low plasticizing efficiency and decreased low-temperature performance, neither of which solves the problem of interfacial weakening caused by white oil migration.
[0006] Existing compatibilizers are mostly maleic anhydride-grafted polypropylene, which has a high molecular weight. During the holding pressure window of two-shot injection molding, it is difficult for them to diffuse rapidly to the TPE surface, resulting in only shallow adsorption at the interface and an inability to form deep entanglement with the TPE molecular chains. Furthermore, existing technologies do not consider utilizing the inherent migration trend of white oil, but rather passively prevent it, failing to transform this destructive factor into a constructive one.
[0007] Therefore, there is a need to design a PP-TPE adhesive-free composite material, its preparation method, and its application. Summary of the Invention
[0008] To overcome the shortcomings of existing technologies, this paper provides a PP-TPE adhesive-free composite material, its preparation method, and its application.
[0009] To achieve the above objectives, the present invention provides the following technical solution: A PP-TPE adhesive-free composite material, comprising a TPE functional layer and a PP matrix layer; The TPE functional layer comprises 40-50 parts of hydrogenated styrene-butadiene-styrene block copolymer, 10-15 parts of homopolymer polypropylene, 8-15 parts of reactive polyisobutylene plasticizer, 3-6 parts of white oil, 8-12 parts of talc, and 0.3-0.5 parts of antioxidant. The PP matrix layer comprises 60-75 parts copolymer polypropylene, 4-8 parts low molecular weight epoxy-grafted polypropylene, 5-10 parts talc, and 0.3-0.6 parts antioxidant. The reactive polyisobutylene plasticizer is obtained by reacting liquid polyisobutylene with maleic anhydride in toluene under the initiation of dicumyl peroxide; The low molecular weight epoxy-grafted polypropylene is obtained by melt grafting isotactic polypropylene and glycidyl methacrylate under the initiation of dicumyl peroxide. The composite material also includes a microcapsule catalyst.
[0010] The preparation of the reactive polyisobutylene plasticizer includes the following steps: dissolving liquid polyisobutylene in toluene, adding maleic anhydride and dicumyl peroxide, reacting at 130-150℃ for 3-5 hours, and removing the anhydride-grafted liquid polyisobutylene under vacuum to obtain the reactive polyisobutylene plasticizer.
[0011] The mass ratio of the liquid polyisobutylene, toluene, maleic anhydride and dicumyl peroxide is 100:(150-250):(5-10):(1-1.5). The number-average molecular weight of the liquid polyisobutylene is 2000-5000.
[0012] The specific parameters for vacuum removal are: removing solvent and unreacted monomers under vacuum conditions of -0.09 MPa and temperature of 120-140℃ for 2-3 hours.
[0013] The preparation of the low molecular weight epoxy-grafted polypropylene includes the following steps: isotactic polypropylene, glycidyl methacrylate, dicumyl peroxide and antioxidant are fed into a twin-screw extruder, and a melt grafting reaction is carried out at 180-200℃. After vacuum devolatilization, low molecular weight epoxy-grafted polypropylene is obtained.
[0014] The mass ratio of isotactic polypropylene, glycidyl methacrylate, dicumyl peroxide, and antioxidant is 100:(6-10):(0.8-1.5):(0.1-0.3). The specific steps and parameters of the vacuum devolatilization are as follows: After the material enters the devolatilization section of the twin-screw extruder, it stays for 30-60 seconds under vacuum of -0.08 MPa and temperature of 180-200℃, and unreacted glycidyl methacrylate, initiator decomposition products and low molecular weight volatiles are extracted.
[0015] The microcapsule catalyst is prepared by the following steps: 2-methylimidazole is mixed with porous silica and adsorbed, then deionized water is added, followed by the addition of melamine-formaldehyde resin prepolymer. The pH is adjusted to 3.0-4.5, and the mixture is stirred at 60-80℃ for 2-4 hours. After filtration, washing, drying, and sieving, microcapsule catalysts with a particle size of 10-30 μm and a wall thickness of 0.5-2 μm are obtained. The mass ratio of the mixture of 2-methylimidazole, porous silica, melamine-formaldehyde resin prepolymer and deionized water is 1:(0.5-1):(3-5):(10-15).
[0016] A method for preparing a PP-TPE adhesive-free composite material includes the following steps: adding hydrogenated styrene-butadiene-styrene block copolymer, homopolymer polypropylene, reactive polyisobutylene plasticizer, white oil, talc powder and antioxidant into an internal mixer and mixing at 160-180℃ for 8-12 minutes, and then granulating by a single screw extruder to obtain TPE granules. Copolymer polypropylene, low molecular weight epoxy-grafted polypropylene, talc and antioxidant are fed into a twin-screw extruder and melt-blended and granulated at 180-200℃ to obtain PP granules. A twin-shot injection molding machine is used. In the first shot, the TPE granules are melted and injected into the mold cavity at 190-210℃ to form a TPE functional layer. The mold temperature is 80-100℃. The second injection involves melting the PP granules at 200-220℃. During the injection of the PP melt into the mold cavity, the microcapsule catalyst is injected into the PP melt in the form of a powder slurry. It is injected into the mold along with the PP melt and combines with the TPE functional layer at the interface. The PP melt injection pressure is 90-130MPa, the holding pressure is 70-90MPa, the holding time is 18-28s, and the composite material is obtained after cooling and solidification.
[0017] The specific steps and parameters for injecting the microcapsule catalyst into the PP melt are as follows: During the second injection of the PP melt into the mold cavity, the microcapsule catalyst is injected into the PP melt in the form of a powder slurry through a liquid additive metering pump in the middle section of the barrel. The powder slurry is prepared by mixing the microcapsule catalyst and liquid paraffin at a mass ratio of 1:1-2. The injection amount of the microcapsule catalyst is 0.5-1.5% of the mass of the PP matrix layer. The surface of the mold cavity on the side forming the TPE functional layer has a V-shaped microgroove array with a groove depth of 5-12 μm and a spacing of 15-40 μm.
[0018] Application of a PP-TPE adhesive-free composite material, which is used to prepare a one-piece molded seat cushion.
[0019] Compared with the prior art, the advantages and beneficial effects of the present invention are as follows: 1. This application uses a reactive polyisobutylene plasticizer to replace part of the white oil. The main chain of this plasticizer is a saturated polyisobutylene structure, which has good compatibility with the rubber phase of the hydrogenated styrene-butadiene-styrene block copolymer. It can insert into the soft segments of the rubber phase to play a plasticizing role and maintain the soft touch of the cushion surface. At the same time, due to its low molecular weight and compatibility with rubber but not chemical bonding, it has a thermodynamic driving force to migrate to the interface during thermal cycling. After migrating to the interface, its side chain anhydride groups can undergo ring-opening esterification with the epoxy groups from the PP matrix layer to form covalent ester bonds. In this way, the white oil migration process, which originally damaged the interface, is transformed into a chemical bridging process that builds the interface, enabling the cushion to achieve continuous interface strengthening during long-term use.
[0020] 2. This application introduces low molecular weight epoxy-grafted polypropylene into the PP matrix layer. The main chain of this compatibilizer is a polypropylene structure, which is entangled and eutectic with the molecular chains of the PP matrix layer. The epoxy groups on the side chains have high reactivity. Due to its low molecular weight and low melt viscosity, it can rapidly diffuse to the TPE surface layer under the high temperature and pressure of the second injection molding, rather than forming a shallow adsorption layer at the interface. After diffusing to the TPE surface layer, the epoxy groups react with the anhydride groups of the reactive polyisobutylene plasticizer that migrated there, forming covalent ester bonds, chemically bonding the TPE layer and the PP matrix layer together, thus solving the problem of shallow interfacial bonding caused by the large molecular weight and slow diffusion of traditional compatibilizers.
[0021] 3. This invention introduces a microcapsule catalyst. First, 2-methylimidazole is adsorbed onto porous silica to form a solid core material, which is then encapsulated by a melamine-formaldehyde resin prepolymer to form a core-shell structure. At room temperature, the 2-methylimidazole is isolated by the wall material, preventing premature contact and reaction with epoxy or anhydride groups. At the high temperature of injection molding, the wall material ruptures and releases the catalyst, instantly catalyzing the ring-opening reaction between the epoxy and anhydride groups, shortening the reaction time from minutes to seconds, matching the holding pressure time window. During the second injection molding, this catalyst is directly injected into the PP melt via a liquid additive metering pump in the middle of the barrel. This avoids the engineering timing contradiction of premature rupture of the microcapsule wall material and catalyst deactivation caused by the PP matrix layer reaching the wall material rupture temperature during twin-screw extrusion granulation, allowing interfacial chemical bridging to be completed within an effective time.
[0022] 4. This invention designs a V-shaped microgroove array on the surface of one side of the TPE functional layer in the mold cavity. The TPE melt replicates the micro-protrusion structure on the surface of the microgrooves. The second injection of PP melt, injected at a higher pressure, fills and encapsulates these micro-protrusions. After cooling, a mechanical anchoring structure is formed at the interface. When the interface is subjected to tearing stress, the PP resin pillars embedded in the gaps between the micro-protrusions provide pull-out resistance, preventing chemical bonds from breaking due to instantaneous overload, providing stress protection for chemical bridging, and ensuring that the interface remains intact under instantaneous load. Attached Figure Description
[0023] Figure 1 This is a process flow diagram of a method for preparing a PP-TPE adhesive-free composite material. Detailed Implementation
[0024] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0025] In the specific embodiments of this application, the sources of various main raw materials are briefly described as follows: Liquid polyisobutylene: purchased from Guangzhou Yinghong Chemical Co., Ltd., grade PB2400, number average molecular weight 2400. Toluene: Purchased from Anhui Zhuotai Chemical Technology Co., Ltd., CAS No. 108-88-3 Maleic anhydride: purchased from Shandong Jinyueyuan New Materials Co., Ltd., CAS No. 108-31-6 Dicumyl peroxide: Purchased from AkzoNobel Peroxides (Ningbo) Co., Ltd., CAS No. 80-43-3, model number BC-FF Isotropic polypropylene: purchased from Dushanzi Petrochemical Branch of China National Petroleum Corporation, grade S1003 Homopolymer polypropylene: purchased from Zhenhai Refining & Chemical Branch of China Petroleum & Chemical Corporation, grade PPH-T03 Hydrogenated styrene-butadiene-styrene block copolymer: purchased from Sinopec Baling Petrochemical Co., Ltd., grade YH-503 Glycidyl methacrylate: Purchased from Wuhan Camick Technology Co., Ltd., purity 99%, CAS number 106-91-2 Antioxidant: Purchased from Tianjin Lianlong New Material Co., Ltd., model: Antioxidant 1010, CAS number: 6683-19-8 2-Methylimidazole: Purchased from Wuhan Jiyesheng Chemical Co., Ltd., CAS No. 693-98-1, industrial grade. Porous silica: purchased from Shijiazhuang Chaowei New Materials Technology Co., Ltd., CAS No. 7631-86-9 Melamine-formaldehyde resin prepolymer: purchased from Jiangsu Sanmu Group Co., Ltd., CAS No. 9003-08-1 White oil: Purchased from Weifang Chenxing Chemical Technology Co., Ltd., CAS No. 8042-47-5 Talc powder: purchased from Liaoning Beihai Industry (Group), industrial grade, 1250 mesh. Copolymer polypropylene: Purchased from Zhenhai Refining & Chemical Branch of China Petroleum & Chemical Corporation, grade EPS30R, specification: high-impact block copolymer polypropylene. Liquid paraffin: purchased from Xinji Haorui Petrochemical Co., Ltd., CAS No. 8012-95-1, industrial grade. The technical solution of this application is as follows: A PP-TPE adhesive-free composite material, comprising a TPE functional layer and a PP matrix layer; The TPE functional layer comprises 40-50 parts of hydrogenated styrene-butadiene-styrene block copolymer, 10-15 parts of homopolymer polypropylene, 8-15 parts of reactive polyisobutylene plasticizer, 3-6 parts of white oil, 8-12 parts of talc, and 0.3-0.5 parts of antioxidant. The PP matrix layer comprises 60-75 parts copolymer polypropylene, 4-8 parts low molecular weight epoxy-grafted polypropylene, 5-10 parts talc, and 0.3-0.6 parts antioxidant. The reactive polyisobutylene plasticizer is obtained by reacting liquid polyisobutylene with maleic anhydride in toluene under the initiation of dicumyl peroxide; The low molecular weight epoxy-grafted polypropylene is obtained by melt grafting isotactic polypropylene and glycidyl methacrylate under the initiation of dicumyl peroxide. The composite material also includes a microcapsule catalyst.
[0026] The preparation of the reactive polyisobutylene plasticizer includes the following steps: dissolving liquid polyisobutylene in toluene, adding maleic anhydride and dicumyl peroxide, reacting at 130-150℃ for 3-5 hours, and removing the solvent under vacuum to obtain anhydride-grafted liquid polyisobutylene, which is the reactive polyisobutylene plasticizer. The mass ratio of liquid polyisobutylene, toluene, maleic anhydride, and dicumyl peroxide is 100:(150-250):(5-10):(1-1.5); the number average molecular weight of the liquid polyisobutylene is 2000-5000. The specific parameters for vacuum removal are: removing the solvent and unreacted monomers under a vacuum of -0.09 MPa and a temperature of 120-140℃ for 2-3 hours.
[0027] In the preparation of a one-piece injection molded seat cushion, after the first injection of the TPE functional layer into the mold, the surface rapidly cools down under the mold's cooling effect, causing a sharp decrease in molecular chain mobility and forming a dense crystalline skin. This skin layer hinders the penetration of the second injection of PP melt and its compatibilizer into the TPE surface, resulting in only a shallow physical contact at the interface, insufficient molecular chain entanglement density, stress concentration, and interfacial delamination during repeated bending. Simultaneously, the white oil added to the TPE functional layer is a small-molecule alkane, compatible with but not chemically bonded to the hydrogenated styrene-butadiene-styrene block copolymer rubber. Under the thermal cycling and stress of long-term use of the seat cushion, the white oil migrates to the interface, accumulating at the interface to form a weak oil layer, gradually destroying the interfacial bond and leading to delamination and debonding. Existing technologies typically delay migration by increasing the amount of compatibilizer or using high-viscosity white oil, but increasing the compatibilizer leads to increased TPE hardness and a worse tactile feel, while high-viscosity white oil has low plasticizing efficiency and decreased low-temperature performance, neither of which solves the problem of interfacial weakening caused by white oil migration.
[0028] To address the aforementioned problem of white oil migration damaging the interface, this application employs a reactive polyisobutylene plasticizer to replace part of the ordinary white oil. This plasticizer is an anhydride-grafted liquid polyisobutylene, with a saturated polyisobutylene main chain structure. Its molecular chain structure is similar to that of the rubber phase of the hydrogenated styrene-butadiene-styrene block copolymer, exhibiting good compatibility. It can insert into the soft segments of the rubber phase, playing a role in plasticizing and reducing hardness, maintaining the soft feel of the cushion surface. Simultaneously, due to its low molecular weight and compatibility with rubber but not chemical bonding, it possesses a thermodynamic driving force for migration to the interface during high injection molding temperatures and subsequent thermal cycling. When it migrates to the interface, the anhydride groups on its side chains become chemical reaction sites, capable of undergoing ring-opening esterification reactions with the epoxy groups from the PP matrix layer to form covalent ester bonds, chemically bonding the TPE functional layer to the PP matrix layer. In this way, the white oil migration process that originally damaged the interface is transformed into a chemical bridging process that builds the interface. During long-term use, even if the reactive polyisobutylene plasticizer continues to migrate slowly, the newly migrated anhydride groups can still react with the residual epoxy groups in the PP matrix layer, thus achieving continuous interface enhancement, rather than the continuous interface weakening caused by white oil migration in the traditional solution.
[0029] The preparation of the low molecular weight epoxy-grafted polypropylene includes the following steps: isotactic polypropylene, glycidyl methacrylate, dicumyl peroxide, and an antioxidant are fed into a twin-screw extruder and subjected to a melt grafting reaction at 180-200℃. After vacuum devolatilization, low molecular weight epoxy-grafted polypropylene is obtained. The mass ratio of isotactic polypropylene, glycidyl methacrylate, dicumyl peroxide, and antioxidant is 100:(6-10):(0.8-1.5):(0.1-0.3). The specific steps and parameters of the vacuum devolatilization process are as follows: The twin-screw extruder is divided into a feeding section, a mixing section, a devolatilization section, and an extrusion section along the material's forward direction. The devolatilization section is located after the mixing section and before the extrusion section. A post-devolatilization port is opened on the barrel of this section and connected to a vacuum pump through a pipeline to create a vacuum section inside the devolatilization section. After the material enters the devolatilization section, it stays for 30-60 seconds under a vacuum of -0.08 MPa and a temperature of 180-200℃. Unreacted glycidyl methacrylate, initiator decomposition products, and low molecular weight volatiles are extracted from the post-devolatilization port, collected by condensation, and discharged. The devolatilized melt is extruded and granulated through the extrusion section to obtain low molecular weight epoxy-grafted polypropylene.
[0030] However, simply using reactive polyisobutylene plasticizers to deliver reactants to the interface is insufficient; the PP matrix layer also requires reactants capable of rapid docking. Existing compatibilizers are mostly maleic anhydride-grafted polypropylene of ordinary molecular weight. Their long molecular chains and high melt viscosity make them difficult to diffuse rapidly to the TPE surface within the holding pressure window of two-shot injection molding. They can only form shallow adsorption at the interface and cannot form deep entanglement and effective chemical bonding with the TPE molecular chains.
[0031] To address the issue of insufficient compatibilizer diffusion, this application introduces low molecular weight epoxy-grafted polypropylene into the PP matrix layer. This compatibilizer is glycidyl methacrylate-grafted polypropylene, with a polypropylene backbone that is entangled and eutectic with the PP matrix layer molecular chains, ensuring the compatibilizer does not detach from the PP matrix. The epoxy groups on the side chains have high reactivity and can undergo ring-opening esterification reactions with acid anhydride groups. Due to its low molecular weight and low melt viscosity, it can rapidly diffuse into the TPE functional layer during the high temperature and pressure of the second injection molding, rather than merely forming a shallow adsorption layer at the interface. Once diffused into the TPE functional layer, the epoxy groups react with the acid anhydride groups of the reactive polyisobutylene plasticizer that migrated there, forming covalent ester bonds that chemically bond the TPE functional layer and the PP matrix layer together. Without the low molecular weight characteristic, the compatibilizer cannot penetrate into the TPE functional layer within the limited holding pressure time, and the reactants cannot effectively bond together.
[0032] Even though the reactive polyisobutylene plasticizer delivers anhydride groups to the interface, and the low molecular weight epoxy-grafted polypropylene diffuses into the TPE functional layer, the ring-opening esterification reaction between the epoxy groups and the anhydride groups still has a slow reaction rate at the injection molding temperature. Without a catalyst, it is extremely difficult to complete effective chemical bonding within the holding pressure time, resulting in insufficient interfacial chemical bridging density and failing to achieve the goal of improving interfacial bonding strength.
[0033] The microcapsule catalyst is prepared by the following steps: 2-methylimidazole is mixed with porous silica and adsorbed, then deionized water is added, followed by the addition of melamine-formaldehyde resin prepolymer. The pH is adjusted to 3.0-4.5, and the mixture is stirred at 60-80℃ for 2-4 hours. After filtration, washing, drying, and sieving, microcapsule catalysts with a particle size of 10-30 μm and a wall thickness of 0.5-2 μm are obtained. The mass ratio of 2-methylimidazole, porous silica, melamine-formaldehyde resin prepolymer, and deionized water is 1:(0.5-1):(3-5):(10-15).
[0034] To address the issue of insufficient reaction kinetics, this application introduces a microcapsule catalyst. This catalyst uses 2-methylimidazole as the core material, which is adsorbed onto porous silica and then encapsulated by a melamine-formaldehyde resin prepolymer to form a core-shell structured microcapsule. At room temperature, the 2-methylimidazole is isolated by the microcapsule wall material, preventing premature contact and reaction with epoxy or anhydride groups. At the high temperature of injection molding, the wall material ruptures and releases the catalyst, instantly catalyzing the ring-opening reaction between the epoxy and anhydride groups, shortening the reaction time from minutes to seconds, matching the holding pressure time window. This catalyst is not pre-mixed into the PP granules but is directly injected into the PP melt during the second injection molding process via a liquid additive metering pump in the middle of the barrel. This avoids the engineering timing contradiction of premature rupture of the microcapsule wall material and catalyst deactivation caused by the PP matrix layer reaching its wall rupture temperature during twin-screw extrusion granulation. The melamine-formaldehyde resin wall material remains intact at the twin-screw extrusion granulation temperature of the PP matrix layer and ruptures to release the core material under the high temperature of the second injection molding and interfacial shearing. Without the acceleration of a catalyst, the chemical reaction at the interface cannot be completed within the effective time, and chemical bridging cannot be achieved.
[0035] A method for preparing a PP-TPE adhesive-free composite material, such as... Figure 1 As shown, the method includes the following steps: hydrogenated styrene-butadiene-styrene block copolymer, homopolymer polypropylene, reactive polyisobutylene plasticizer, white oil, talc powder and antioxidant are put into an internal mixer and mixed at 160-180℃ for 8-12 minutes, and then granulated by a single screw extruder to obtain TPE granules. Copolymer polypropylene, low molecular weight epoxy-grafted polypropylene, talc and antioxidant are fed into a twin-screw extruder and melt-blended and granulated at 180-200℃ to obtain PP granules. A twin-shot injection molding machine is used. In the first shot, the TPE granules are melted and injected into the mold cavity at 190-210℃ to form a TPE functional layer. The mold temperature is 80-100℃. The second injection involves melting the PP granules at 200-220℃. During the injection of the PP melt into the mold cavity, the microcapsule catalyst is injected into the PP melt in the form of a powder slurry. It is injected into the mold along with the PP melt and combines with the TPE functional layer at the interface. The PP melt injection pressure is 90-130MPa, the holding pressure is 70-90MPa, the holding time is 18-28s, and the composite material is obtained after cooling and solidification.
[0036] The specific steps and parameters for injecting the microcapsule catalyst into the PP melt are as follows: During the second injection of the PP melt into the mold cavity, the microcapsule catalyst is injected into the PP melt in the form of a powder slurry through a liquid additive metering pump in the middle section of the barrel. The powder slurry is prepared by mixing the microcapsule catalyst and liquid paraffin at a mass ratio of 1:1-2. The injection amount of the microcapsule catalyst is 0.5-1.5% of the mass of the PP matrix layer. The surface of the mold cavity on the side forming the TPE functional layer has a V-shaped microgroove array with a groove depth of 5-12 μm and a spacing of 15-40 μm.
[0037] While chemical bridging provides strong interfacial bonding, pure chemical bonds can still break under instantaneous tearing stress. Existing technologies often have overly smooth interfaces lacking physical anchoring; once chemical bonds break, cracks propagate rapidly along the interface, leading to delamination failure. To address the insufficient overload resistance of the interface, this application designs a V-shaped microgroove array on the surface of one side of the TPE functional layer formed in the mold cavity. The TPE melt replicates on the microgroove surface, forming corresponding micro-protrusion structures on the surface of the TPE functional layer. A second injection of PP melt is injected at higher pressure, filling and encapsulating these micro-protrusions. After cooling, a rivet-like mechanical anchoring structure is formed at the interface. When the interface is subjected to tearing stress, the PP resin pillars embedded in the gaps between the micro-protrusions provide pull-out resistance, preventing chemical bonds from breaking due to instantaneous overload. Without the mechanical interlocking of the microgrooves, chemical bridging lacks protection under instantaneous overload, resulting in insufficient interfacial reliability.
[0038] Application of a PP-TPE adhesive-free composite material, which is used to prepare a one-piece molded seat cushion.
[0039] The present invention will be described in detail below through examples and comparative examples, but the scope of protection of the present invention is not limited to these examples. Unless otherwise specified, the chemical reagents and raw materials used in the following examples and comparative examples are all conventional commercially available products.
[0040] Example 1 100 parts of liquid polyisobutylene were mixed and dissolved with 200 parts of toluene. 5 parts of maleic anhydride and 1.5 parts of dicumyl peroxide were added, and the mixture was reacted at 140℃ for 3 hours. After the reaction was completed, the solvent and unreacted monomers were removed under vacuum of -0.09 MPa and temperature of 140℃ for 2.5 hours to obtain a reactive polyisobutylene plasticizer.
[0041] 100 parts of isotactic polypropylene, 10 parts of glycidyl methacrylate, 1.15 parts of dicumyl peroxide and 0.1 parts of antioxidant were fed into a twin-screw extruder and subjected to a melt grafting reaction at 200°C. After the material entered the devolatilization section, it was held for 45 seconds under a vacuum of -0.08 MPa and a temperature of 190°C to remove volatiles. The material was then extruded and granulated to obtain low molecular weight epoxy grafted polypropylene.
[0042] One part of 2-methylimidazole was mixed with one part of porous silica for adsorption, and then 10 parts of deionized water and 4 parts of melamine-formaldehyde resin prepolymer were added. The pH was adjusted to 4.5, and the mixture was stirred at 1000 r / min and 70℃ for 2 h. After filtration, washing, drying and sieving, microcapsule catalysts with a particle size of 20 μm and a wall thickness of 2.0 μm were obtained.
[0043] 50 parts of hydrogenated styrene-butadiene-styrene block copolymer, 12.5 parts of homopolymer polypropylene, 8 parts of reactive polyisobutylene plasticizer, 6 parts of white oil, 10 parts of talc, and 0.3 parts of antioxidant were added to an internal mixer and mixed at 180°C for 10 minutes. The mixture was then granulated using a single-screw extruder at 170°C to obtain TPE granules. 75 parts of copolymer polypropylene, 6 parts of low molecular weight epoxy-grafted polypropylene, 5 parts of talc, and 0.6 parts of antioxidant were added to a twin-screw extruder and melt-blended and granulated at 190°C to obtain PP granules.
[0044] A dual-injection molding machine was used. The surface of the mold cavity forming the TPE functional layer had a V-shaped microgroove array with a groove depth of 5 μm and a spacing of 27.5 μm. The first injection melted TPE granules at 210℃ and injected them into the mold cavity to form the TPE functional layer; the mold temperature was 90℃. The second injection melted PP granules at 200℃. During the injection of the PP melt into the mold cavity, a microcapsule catalyst was injected into the PP melt in the form of a powder slurry through a liquid additive metering pump in the middle of the barrel. The powder slurry was prepared by mixing the microcapsule catalyst and liquid paraffin at a mass ratio of 1:1.5. The injection amount of the microcapsule catalyst was 1.5% of the mass of the PP matrix layer. It was injected into the mold along with the PP melt and bonded to the TPE functional layer at the interface. The PP melt injection pressure was 130 MPa, the holding pressure was 80 MPa, and the holding time was 18 s. After cooling and solidification, the composite material was obtained.
[0045] Example 2 100 parts of liquid polyisobutylene were mixed and dissolved with 250 parts of toluene. 7.5 parts of maleic anhydride and 1.0 part of dicumyl peroxide were added, and the mixture was reacted at 150°C for 4 hours. After the reaction was completed, the solvent and unreacted monomers were removed under vacuum of -0.09 MPa and temperature of 120°C for 3 hours to obtain a reactive polyisobutylene plasticizer.
[0046] 100 parts of isotactic polypropylene, 6 parts of glycidyl methacrylate, 1.5 parts of dicumyl peroxide and 0.2 parts of antioxidant were fed into a twin-screw extruder and subjected to a melt grafting reaction at 180°C. After the material entered the devolatilization section, it was held for 60 seconds under a vacuum of -0.08 MPa and a temperature of 200°C to remove volatiles. The material was then extruded and granulated to obtain low molecular weight epoxy-grafted polypropylene.
[0047] One part of 2-methylimidazole was mixed with 0.5 parts of porous silica for adsorption. 12.5 parts of deionized water were added, followed by 5 parts of melamine-formaldehyde resin prepolymer. The pH was adjusted to 3.0, and the mixture was stirred at 1500 r / min and 80℃ for 3 h. After filtration, washing, drying, and sieving, microcapsule catalysts with a particle size of 10 μm and a wall thickness of 0.8 μm were obtained.
[0048] Forty parts of hydrogenated styrene-butadiene-styrene block copolymer, 15 parts of homopolymer polypropylene, 11.5 parts of reactive polyisobutylene plasticizer, 3 parts of white oil, 12 parts of talc, and 0.4 parts of antioxidant were added to an internal mixer and mixed at 160°C for 12 minutes. The mixture was then granulated using a single-screw extruder at 170°C to obtain TPE granules. For PP granules, 60 parts of copolymer polypropylene, 8 parts of low molecular weight epoxy-grafted polypropylene, 7.5 parts of talc, and 0.3 parts of antioxidant were added to a twin-screw extruder and melt-blended and granulated at 190°C.
[0049] A dual-injection molding machine was used. The surface of the mold cavity on the side forming the TPE functional layer has a V-shaped microgroove array with a groove depth of 12 μm and a spacing of 27.5 μm. The first injection melts TPE granules at 190℃ and injects them into the mold cavity to form the TPE functional layer; the mold temperature is 100℃. The second injection melts PP granules at 210℃. During the injection of the PP melt into the mold cavity, a microcapsule catalyst is injected into the PP melt in the form of a powder slurry through a liquid additive metering pump in the middle of the barrel. The powder slurry is prepared by mixing the microcapsule catalyst and liquid paraffin at a mass ratio of 1:2. The injection amount of the microcapsule catalyst is 0.5% of the mass of the PP matrix layer. It is injected into the mold along with the PP melt and bonds with the TPE functional layer at the interface. The PP melt injection pressure is 90 MPa, the holding pressure is 90 MPa, the holding time is 23 s, and cooling and solidification yield the composite material.
[0050] Example 3 In this embodiment, the similarities to those in Embodiment 1 will not be repeated, and the differences are as follows: 100 parts of liquid polyisobutylene were mixed and dissolved with 150 parts of toluene, and 10 parts of maleic anhydride and 1.25 parts of dicumyl peroxide were added. The mixture was reacted at 130°C for 5 hours. After the reaction was completed, the solvent and unreacted monomers were removed under vacuum of -0.09 MPa and temperature of 130°C for 2 hours to obtain a reactive polyisobutylene plasticizer.
[0051] 100 parts of isotactic polypropylene, 8 parts of glycidyl methacrylate, 0.8 parts of dicumyl peroxide and 0.3 parts of antioxidant were fed into a twin-screw extruder and subjected to a melt grafting reaction at 190°C. After the material entered the devolatilization section, it was held for 30 seconds under a vacuum of -0.08 MPa and a temperature of 180°C to remove volatiles. The material was then extruded and granulated to obtain low molecular weight epoxy grafted polypropylene.
[0052] One part of 2-methylimidazole was mixed with 0.75 parts of porous silica for adsorption. 15 parts of deionized water were added, followed by 3 parts of melamine-formaldehyde resin prepolymer. The pH was adjusted to 3.75, and the mixture was stirred at 600 r / min and 60℃ for 4 h. After filtration, washing, drying, and sieving, microcapsule catalysts with a particle size of 30 μm and a wall thickness of 1.4 μm were obtained.
[0053] 45 parts of hydrogenated styrene-butadiene-styrene block copolymer, 10 parts of homopolymer polypropylene, 15 parts of reactive polyisobutylene plasticizer, 4.5 parts of white oil, 8 parts of talc, and 0.5 parts of antioxidant were added to an internal mixer and mixed at 170°C for 8 minutes. The mixture was then granulated using a single-screw extruder at 170°C to obtain TPE granules. 67.5 parts of copolymer polypropylene, 4 parts of low molecular weight epoxy-grafted polypropylene, 10 parts of talc, and 0.45 parts of antioxidant were added to a twin-screw extruder and melt-blended and granulated at 190°C to obtain PP granules.
[0054] A dual-injection molding machine was used. The surface of the mold cavity on the side forming the TPE functional layer had a V-shaped microgroove array with a groove depth of 8.5 μm and a spacing of 27.5 μm. The first injection melted TPE granules at 200°C and injected them into the mold cavity to form the TPE functional layer; the mold temperature was 80°C. The second injection melted PP granules at 220°C. During the injection of the PP melt into the mold cavity, a microcapsule catalyst was injected into the PP melt in the form of a powder slurry through a liquid additive metering pump in the middle of the barrel. The powder slurry was prepared by mixing the microcapsule catalyst and liquid paraffin at a mass ratio of 1:1. The injection amount of the microcapsule catalyst was 1.0% of the mass of the PP matrix layer. It was injected into the mold along with the PP melt and bonded to the TPE functional layer at the interface. The PP melt injection pressure was 110 MPa, the holding pressure was 70 MPa, and the holding time was 28 s. After cooling and solidification, the composite material was obtained.
[0055] Example 4 In this embodiment, the similarities to those in Embodiment 1 will not be repeated, and the differences are as follows: 100 parts of liquid polyisobutylene were mixed and dissolved with 200 parts of toluene. 8 parts of maleic anhydride and 1.2 parts of dicumyl peroxide were added, and the mixture was reacted at 140℃ for 4 hours. After the reaction was completed, the solvent and unreacted monomers were removed under vacuum of -0.09 MPa and temperature of 130℃ for 2.5 hours to obtain a reactive polyisobutylene plasticizer.
[0056] 100 parts of isotactic polypropylene, 8 parts of glycidyl methacrylate, 1.2 parts of dicumyl peroxide and 0.2 parts of antioxidant were fed into a twin-screw extruder and subjected to a melt grafting reaction at 190°C. After the material entered the devolatilization section, it was held for 45 seconds under a vacuum of -0.08 MPa and a temperature of 190°C to remove volatiles. The material was then extruded and granulated to obtain low molecular weight epoxy grafted polypropylene.
[0057] One part of 2-methylimidazole was mixed with 0.75 parts of porous silica for adsorption. 12.5 parts of deionized water were added, followed by 4 parts of melamine-formaldehyde resin prepolymer. The pH was adjusted to 3.5, and the mixture was stirred at 1000 r / min and 70℃ for 3 h. After filtration, washing, drying, and sieving, microcapsule catalysts with a particle size of 20 μm and a wall thickness of 1.2 μm were obtained.
[0058] 45 parts of hydrogenated styrene-butadiene-styrene block copolymer, 12 parts of homopolymer polypropylene, 12 parts of reactive polyisobutylene plasticizer, 4 parts of white oil, 10 parts of talc, and 0.4 parts of antioxidant were added to an internal mixer and mixed at 170°C for 10 minutes. The mixture was then granulated using a single-screw extruder at 170°C to obtain TPE granules. 68 parts of copolymer polypropylene, 6 parts of low molecular weight epoxy-grafted polypropylene, 7.5 parts of talc, and 0.45 parts of antioxidant were added to a twin-screw extruder and melt-blended and granulated at 190°C to obtain PP granules.
[0059] A dual-injection molding machine was used. The surface of the mold cavity on the side forming the TPE functional layer has a V-shaped microgroove array with a groove depth of 8 μm and a spacing of 27.5 μm. The first injection melts TPE granules at 200℃ and injects them into the mold cavity to form the TPE functional layer; the mold temperature is 90℃. The second injection melts PP granules at 210℃. During the injection of the PP melt into the mold cavity, a microcapsule catalyst is injected into the PP melt in the form of a powder slurry through a liquid additive metering pump in the middle of the barrel. The powder slurry is prepared by mixing the microcapsule catalyst and liquid paraffin at a mass ratio of 1:1.5. The injection amount of the microcapsule catalyst is 1.0% of the mass of the PP matrix layer. It is injected into the mold along with the PP melt and bonds with the TPE functional layer at the interface. The PP melt injection pressure is 110 MPa, the holding pressure is 80 MPa, and the holding time is 22 s. After cooling and solidification, the composite material is obtained.
[0060] Comparative Example 1 Compared with Example 1, the difference is that reactive polyisobutylene plasticizer is not used in the TPE functional layer. Instead, white oil is used entirely, which consists of 50 parts of hydrogenated styrene-butadiene-styrene block copolymer, 12.5 parts of homopolymer polypropylene, 14 parts of white oil, 10 parts of talc, and 0.4 parts of antioxidant. The rest is the same as in Example 1.
[0061] Comparative Example 2 Compared with Example 2, the difference is that ordinary molecular weight epoxy-grafted polypropylene is used instead of low molecular weight epoxy-grafted polypropylene in the PP matrix layer. The weight average molecular weight of ordinary molecular weight epoxy-grafted polypropylene is about 50,000, and the amount used is 8 parts. Everything else is the same as in Example 2.
[0062] Comparative Example 3 Compared with Example 3, the difference is that microcapsule catalysts are not used. Instead, 0.05 parts of 2-methylimidazole powder are directly mixed into the PP matrix layer. Otherwise, it is the same as Example 3.
[0063] Comparative Example 4 Compared with Example 4, the difference is that the surface on the side where the TPE functional layer is formed in the mold cavity is a smooth surface without a V-shaped microgroove array, while the rest is the same as Example 4.
[0064] Comparative Example 5 Compared with Example 1, the difference is that 10 parts of light calcium carbonate are used instead of 10 parts of talc in the TPE functional layer, otherwise it is the same as Example 1.
[0065] Performance Test Results and Analysis The PP-TPE adhesive-free composite material samples prepared in Examples 1 to 4 and Comparative Examples 1 to 5 were cut and tested as follows. The interfacial peel strength test was conducted according to ASTM D1876 standard. The samples were cut into T-shaped peel specimens with a total length of 150 mm, a width of 25 mm, a TPE functional layer thickness of 2 mm, and a PP matrix layer thickness of 8 mm. Before testing, the samples were conditioned for 24 hours at 23±2℃ and 50±5% relative humidity. The test was performed using a universal testing machine at a peel rate of 100 mm / min. The average force during the peeling process was recorded, and the interfacial peel strength was calculated in N / mm.
[0066] Bending fatigue life testing was conducted using a reciprocating bending fatigue testing machine. The specimen was cut into a rectangular piece of 50mm×100mm, with a bending angle of 180° and a frequency of 60 cycles / min. The machine was stopped every 1000 cycles to check the interface condition. The appearance of through cracks or visible delamination at the interface was used as the failure criterion, and the number of cycles at the time of failure was recorded.
[0067] For the test of the retention rate of interfacial peel strength after damp heat aging, the above peel strength samples were placed in a constant temperature and humidity test chamber at 85℃ and 85% relative humidity for 500 hours. After aging, the samples were taken out and placed in a standard environment at 23±2℃ and 50±5% relative humidity for 24 hours. The interfacial peel strength was then measured according to the test method. The ratio of the strength after aging to the strength before aging was calculated and expressed as a percentage.
[0068] The interfacial chemical bonding density was measured using X-ray photoelectron spectroscopy. A narrow C1s scan was performed at the interface, and the degree of interfacial chemical bonding was characterized by the ratio of the characteristic peak area of ester bond C=O to the total carbon peak area, expressed as a percentage.
[0069] The interfacial shear strength test adopted the lap shear method. The specimen was cut into a rectangular piece of 25mm × 100mm, with an overlap length of 25mm and a width of 25mm. The test was conducted using a universal testing machine at a tensile rate of 1.3mm / min. The maximum load at failure was recorded, and the interfacial shear strength was calculated in MPa. The test results are shown in Table 1.
[0070] As can be seen from Table 1, the performance indicators of Examples 1 to 4 are all superior to those of Comparative Examples 1 to 5, indicating that the technical solution of this application can effectively improve the interfacial bonding performance of PP-TPE adhesive-free composite materials. The worst interfacial peel strength in the examples is 7.2 N / mm, which is higher than the highest 6.5 N / mm in the comparative examples. The bending fatigue life, damp heat aging retention rate, relative content of interfacial ester bonds, and interfacial shear strength all show the same trend.
[0071] Compared to Example 1, Comparative Example 1 did not use reactive polyisobutylene plasticizer in the TPE functional layer; instead, it used only white oil. White oil is a small-molecule alkane, compatible with hydrogenated styrene-butadiene-styrene block copolymer rubber but not chemically bonded. During long-term use, it migrates to the interface, forming a low-surface-energy lubricating layer. This lubricating layer hinders the molecular chain entanglement between PP and TPE. Furthermore, due to the lack of anhydride groups, it cannot undergo ring-opening esterification with the epoxy groups from the PP matrix layer. The relative content of interfacial ester bonds is only 4.5%, far lower than the 18.5% in Example 1. This results in an interfacial peel strength of only 3.2 N / mm, a bending fatigue life of only 30,000 cycles, and an interfacial peel strength retention rate of only 45% after humid heat aging. From a molecular perspective, the enrichment of white oil molecules at the interface reduces the cohesive energy density at the interface, making the interface more prone to molecular chain slippage and deentanglement under humid heat conditions, thus leading to severe strength degradation after aging.
[0072] Compared to Example 2, Comparative Example 2 used ordinary molecular weight epoxy-grafted polypropylene instead of low molecular weight epoxy-grafted polypropylene in the PP matrix layer. The weight-average molecular weight of ordinary molecular weight epoxy-grafted polypropylene is approximately 50,000. According to Fick's diffusion law, the diffusion coefficient is inversely proportional to molecular weight. High molecular weight compatibilizers have high melt viscosity and low diffusion coefficients. Within the holding time (23 seconds), their penetration depth is limited, and they can only form shallow adsorption at the interface, unable to penetrate into the dense crystalline region of the TPE surface. Therefore, the epoxy group concentration at the interface is low, the relative content of interfacial ester bonds is only 6.8%, lower than 16.8% in Example 2, the interfacial peel strength is only 4.1 N / mm, and the interfacial shear strength is only 3.2 MPa. In contrast, low molecular weight epoxy-grafted polypropylene, due to its short molecular chain and low melt viscosity, has a diffusion coefficient an order of magnitude higher than that of ordinary molecular weight compatibilizers, enabling it to penetrate into the TPE surface within the holding time and fully react with the migrating anhydride groups.
[0073] Compared to Example 3, Comparative Example 3 did not use a microencapsulated catalyst; instead, 2-methylimidazole powder was directly mixed into the PP matrix layer. During the twin-screw extrusion granulation and injection molding of the PP matrix layer, 2-methylimidazole was immediately released at high temperature, catalyzing the homopolymerization of epoxy groups within the PP matrix and consuming a large number of active groups originally intended for interfacial reactions. Simultaneously, the free-state catalyst was uniformly distributed in the PP melt, and its concentration decreased significantly by the time it reached the interface, failing to effectively catalyze the anhydride-epoxy reaction at the interface. Therefore, the relative content of interfacial ester bonds was only 5.6%, lower than the 18.9% in Example 3, and the interfacial peel strength was only 3.8 N / mm. Furthermore, the homopolymerization of epoxy groups within the PP matrix led to a localized increase in melt viscosity, potentially causing uneven flow during injection molding and further affecting interfacial quality.
[0074] Compared to Example 4, Comparative Example 4 has a smooth surface on the side of the mold cavity where the TPE functional layer is formed, without the V-shaped microgroove array. The smooth interface is a planar contact with a high stress concentration factor. Under instantaneous tearing stress, the chemical bonds bear the entire load, making them prone to breakage due to overload. The interfacial shear strength is only 4.5 MPa, lower than the 7.8 MPa of Example 4, and the bending fatigue life is only 60,000 cycles. In contrast, the microgroove structure increases the actual contact area. After the PP melt fills and encapsulates the micro-protrusions, it forms a mechanical anchor. Stress is dispersed and transferred through the anchoring structure, significantly reducing the stress borne by the chemical bonds, and the interface can remain intact under instantaneous load.
[0075] Compared to Example 1, Comparative Example 5 used 10 parts of light calcium carbonate instead of 10 parts of talc in the TPE functional layer. Light calcium carbonate is an alkaline filler; its surface hydroxyl groups and carbonate groups in the crystal lattice can react with the anhydride groups of the reactive polyisobutylene plasticizer to form calcium carboxylate, significantly consuming the anhydride groups required for the interfacial reaction. Therefore, the relative content of interfacial ester bonds is only 3.2%, the lowest among all comparative examples, with an interfacial peel strength of only 2.8 N / mm and an interfacial shear strength of only 2.1 MPa. This verifies the importance of talc as an inert filler; its surface silicate structure does not react with anhydride groups, protecting the active groups for interfacial chemical bridging.
[0076] The differences between Examples 1 to 4 reflect the influence of parameter distribution on interfacial properties. Example 4 represents the optimal combination: 12 parts reactive polyisobutylene plasticizer, 6 parts low molecular weight epoxy-grafted polypropylene, 1.0% microcapsule catalyst injection, and a trench depth of 8 μm. All parameters are within the optimal matching range, the supply of anhydride groups and the diffusion of epoxy groups are balanced, the amount of catalyst is sufficient, the mechanical anchoring depth is moderate, the interfacial peel strength reaches 9.5 N / mm, the bending fatigue life reaches 150,000 cycles, and the retention rate after damp heat aging reaches 92%.
[0077] In Example 1, the reactive polyisobutylene plasticizer was 8 parts with a number-average molecular weight of 5000, and the amount of maleic anhydride was 5 parts. The supply of anhydride groups was relatively small, and the holding time was only 18s. The reaction time between the anhydride groups and epoxy groups at the interface was insufficient, the relative content of interfacial ester bonds was 18.5%, and the interfacial peel strength was 7.8 N / mm. In addition, the trench depth was only 5 μm, the mechanical interlocking depth was shallow, and the interfacial shear strength was 6.2 MPa.
[0078] Table 1 Analysis of Test Results Example 1 7.8 10.5 85 18.5 6.2 Example 2 7.2 9.5 82 16.8 5.8 Example 3 8.0 11 87 18.9 6.5 Example 4 9.5 15 92 22.3 7.8 Comparative Example 1 3.2 3 45 4.5 2.5 Comparative Example 2 4.1 4 52 6.8 3.2 Comparative Example 3 3.8 3.5 48 5.6 2.8 Comparative Example 4 6.5 6 65 12.1 4.5 Comparative Example 5 2.8 2.5 40 3.2 2.1 In Example 2, the microcapsule catalyst had a particle size of 10 μm and a wall thickness of 0.8 μm, with the least amount of wall material and the thinnest wall thickness. While the small particle size is beneficial for dispersion, the thin-walled material has relatively weak shear resistance in the PP melt, and some catalyst may break prematurely in the barrel, leading to the consumption of epoxy groups inside the PP matrix and a reduction in active groups available for interfacial reactions. Simultaneously, the catalyst injection amount was only 0.5%, resulting in insufficient catalyst at the interface, with a relative ester bond content of 16.8%, lower than in Example 1. However, the trench depth was 12 μm, the deepest among all examples, providing strong mechanical interlocking and compensating for the shortcomings of chemical bridging. The interfacial peel strength was 7.2 N / mm, and the interfacial shear strength was 5.8 MPa.
[0079] In Example 3, the reactive polyisobutylene plasticizer was 15 parts, and the maleic anhydride was 10 parts, ensuring a sufficient supply of anhydride groups. The holding time was 28 seconds, providing the longest reaction time window and facilitating a full reaction between the anhydride groups and epoxy groups. However, the low molecular weight epoxy-grafted polypropylene was only 4 parts, resulting in a relatively insufficient supply of epoxy groups, which limited further increases in chemical bonding content. The relative content of interfacial ester bonds was 18.9%, falling between that of Examples 1 and 4. The interfacial peel strength was 8.0 N / mm, and the bending fatigue life was 110,000 cycles.
[0080] Test results show that this application provides anhydride groups to the interface through reactive polyisobutylene plasticizer, provides epoxy groups through rapid diffusion of low molecular weight epoxy-grafted polypropylene, catalyzes the formation of ester bonds between the two at the interface through microcapsule catalyst, and provides mechanical anchoring through mold microgrooves, so that the PP-TPE adhesive-free composite cushion maintains interface stability during long-term use, does not crack when bent, and does not delaminate when torn.
[0081] The above description represents the preferred embodiments of the present invention. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A PP-TPE adhesive-free composite material, characterized in that, The composite material includes a TPE functional layer and a PP matrix layer; The TPE functional layer comprises 40-50 parts of hydrogenated styrene-butadiene-styrene block copolymer, 10-15 parts of homopolymer polypropylene, 8-15 parts of reactive polyisobutylene plasticizer, 3-6 parts of white oil, 8-12 parts of talc, and 0.3-0.5 parts of antioxidant. The PP matrix layer comprises 60-75 parts copolymer polypropylene, 4-8 parts low molecular weight epoxy-grafted polypropylene, 5-10 parts talc, and 0.3-0.6 parts antioxidant. The reactive polyisobutylene plasticizer is obtained by reacting liquid polyisobutylene with maleic anhydride in toluene under the initiation of dicumyl peroxide; The low molecular weight epoxy-grafted polypropylene is obtained by melt grafting isotactic polypropylene and glycidyl methacrylate under the initiation of dicumyl peroxide. The composite material also includes a microcapsule catalyst.
2. The PP-TPE adhesive-free composite material according to claim 1, characterized in that, The preparation of the reactive polyisobutylene plasticizer includes the following steps: dissolving liquid polyisobutylene in toluene, adding maleic anhydride and dicumyl peroxide, reacting at 130-150℃ for 3-5 hours, and removing the anhydride-grafted liquid polyisobutylene under vacuum to obtain the reactive polyisobutylene plasticizer.
3. The PP-TPE adhesive-free composite material according to claim 2, characterized in that, The mass ratio of the liquid polyisobutylene, toluene, maleic anhydride and dicumyl peroxide is 100:(150-250):(5-10):(1-1.5). The number-average molecular weight of the liquid polyisobutylene is 2000-5000.
4. The PP-TPE adhesive-free composite material according to claim 2, characterized in that, The specific parameters for vacuum removal are: removing solvent and unreacted monomers under vacuum conditions of -0.09 MPa and temperature of 120-140℃ for 2-3 hours.
5. The PP-TPE adhesive-free composite material according to claim 1, characterized in that, The preparation of the low molecular weight epoxy-grafted polypropylene includes the following steps: isotactic polypropylene, glycidyl methacrylate, dicumyl peroxide and antioxidant are fed into a twin-screw extruder, and a melt grafting reaction is carried out at 180-200℃. After vacuum devolatilization, low molecular weight epoxy-grafted polypropylene is obtained.
6. The PP-TPE adhesive-free composite material according to claim 5, characterized in that, The mass ratio of isotactic polypropylene, glycidyl methacrylate, dicumyl peroxide, and antioxidant is 100:(6-10):(0.8-1.5):(0.1-0.3). The specific steps and parameters of the vacuum devolatilization are as follows: After the material enters the devolatilization section of the twin-screw extruder, it stays for 30-60 seconds under vacuum of -0.08 MPa and temperature of 180-200℃, and unreacted glycidyl methacrylate, initiator decomposition products and low molecular weight volatiles are extracted.
7. The PP-TPE adhesive-free composite material according to claim 1, characterized in that, The microcapsule catalyst is prepared by the following steps: 2-methylimidazole is mixed with porous silica and adsorbed, then deionized water is added, followed by the addition of melamine-formaldehyde resin prepolymer. The pH is adjusted to 3.0-4.5, and the mixture is stirred at 60-80℃ for 2-4 hours. After filtration, washing, drying, and sieving, microcapsule catalysts with a particle size of 10-30 μm and a wall thickness of 0.5-2 μm are obtained. The mass ratio of the mixture of 2-methylimidazolium, porous silica, melamine-formaldehyde resin prepolymer and deionized water is 1:(0.5-1):(3-5):(10-15).
8. A method for preparing a PP-TPE adhesive-free composite material as described in any one of claims 1-7, characterized in that, The method includes the following steps: hydrogenated styrene-butadiene-styrene block copolymer, homopolymer polypropylene, reactive polyisobutylene plasticizer, white oil, talc powder and antioxidant are put into an internal mixer and mixed at 160-180℃ for 8-12 minutes, and then granulated by a single screw extruder to obtain TPE granules. Copolymer polypropylene, low molecular weight epoxy-grafted polypropylene, talc and antioxidant are fed into a twin-screw extruder and melt-blended and granulated at 180-200℃ to obtain PP granules. A twin-shot injection molding machine is used. In the first shot, the TPE granules are melted and injected into the mold cavity at 190-210℃ to form a TPE functional layer. The mold temperature is 80-100℃. The second injection involves melting the PP granules at 200-220℃. During the injection of the PP melt into the mold cavity, the microcapsule catalyst is injected into the PP melt in the form of a powder slurry. It is injected into the mold along with the PP melt and combines with the TPE functional layer at the interface. The PP melt injection pressure is 90-130MPa, the holding pressure is 70-90MPa, the holding time is 18-28s, and the composite material is obtained after cooling and solidification.
9. The method for preparing a PP-TPE adhesive-free composite material according to claim 8, characterized in that, The specific steps and parameters for injecting the microcapsule catalyst into the PP melt are as follows: During the second injection of the PP melt into the mold cavity, the microcapsule catalyst is injected into the PP melt in the form of a powder slurry through a liquid additive metering pump in the middle section of the barrel. The powder slurry is prepared by mixing the microcapsule catalyst and liquid paraffin at a mass ratio of 1:1-2. The injection amount of the microcapsule catalyst is 0.5-1.5% of the mass of the PP matrix layer. The surface of the mold cavity on the side forming the TPE functional layer has a V-shaped microgroove array with a groove depth of 5-12 μm and a spacing of 15-40 μm.
10. An application of the PP-TPE adhesive-free composite material as described in any one of claims 1-7, characterized in that, The composite material is used to prepare a one-piece molded seat cushion.